Les Activités Expérimentales Dans L’enseignement Des Sciences Physiques: Cas Des Collèges Marocains - Mohamed Taoufik; Abderrahim Abouzaid; Ahmed Moufti (European Scientific Journal, ESJ, 2016)
We focused in this article on two essential points: infrastructure dedicated to experimental activities in physics education in Moroccan colleges and experimental practice of teachers and the opinion of students on these activities. The results showed that school laboratories do not facilitate the learning and development of knowledge and know-how of the learners. The experiences of the course, according to teachers and students, are made as of experiences integrated into the course (performed by the teacher himself), the teachers refer to the lack of material, dangerous nature of certain experiences, inadequate premises suitable for practical work, poor management of laboratories that influence the rate of planned experiments and the experimental practices of teachers. The Information and Communication Technologies (ICT) would be a good way to supplement the experiences and not replace them. Teachers argue that the constraints and difficulties related to the integration of ICT are mainly due to an infrastructure deficit and support (training).